Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1097/md.0000000000030515
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic efficacy of the superficial versus deep serratus plane blocks for mastectomy with axillary clearance: A randomized controlled trial

Abstract: Background: The serratus plane block is an effective technique for providing analgesia to patients undergoing breast surgery. Methods: This prospective, double-blind, randomized study enrolled 60 female patients scheduled for unilateral mastectomy and axillary clearance. The patients received either a superficial serratus plane block or deep serratus plane block. Dermatomal spread was recorded 30 minutes after block administration. Postoperatively, pain visual analog scale (VAS) scores were documented at rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In the current study, we have chosen the superficial rather than the deep block, depending on the authors' experience and recommendations from previous studies. Tan et al [16] found that the superficial block achieved better analgesic efficacy for mastectomy with axillary clearance than the deep block, with lower pain scores, longer analgesic time, and reduced morphine consumption. This is probably explained by the need to extend the surgical incision to the lateral aspect of the hemithorax for axillary lymph node dissection.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we have chosen the superficial rather than the deep block, depending on the authors' experience and recommendations from previous studies. Tan et al [16] found that the superficial block achieved better analgesic efficacy for mastectomy with axillary clearance than the deep block, with lower pain scores, longer analgesic time, and reduced morphine consumption. This is probably explained by the need to extend the surgical incision to the lateral aspect of the hemithorax for axillary lymph node dissection.…”
Section: Discussionmentioning
confidence: 99%